Study of Histopathological Variants of Orofacial Lipoma in a Nigerian Population - O.F. Omoregie; O. Akpata; M.A. Ojo (Nigerian Dental Association, 2020)
Background: The rarity of lipoma in the orofacial region has made it difficult to ascertain the clinicopathological pattern of orofacial lipoma in our environment. This study aims to determine the age, gender, sites and histopathological variants of orofacial lipoma in a Nigerian population. Materials and Methods: A 21-year retrospective review was performed on patients' clinical notes, histopathology slides and reports of all histopathologically diagnosed orofacial lesions in the Department of Oral Pathology and Medicine, University of Benin Teaching Hospital, Benin City, Nigeria. Results: Of the 1116 diagnosed lesions within the study period, there were 15 (1.3%) cases of lipoma. There was a female to male ratio of 2:1, with a mean th age of 31 + 1.2 years and the peak age group was the 4 decade of life (n=6, 40.0%). The buccal mucosa (n=8, 53.3%) and the forehead (n=4, 26.7%) were the commonest orofacial sites of the lesion. The conventional lipoma (n=8, 53.3%) was the predominant lesion, followed by angiolipoma (n=3, 20.0%), fibrolipoma (n=2, 13.3%), spindle cell lipoma (n=1, 6.7%) and intramuscular lipoma (n=1, 6.7%). Conclusion: This study observed a low prevalence of orofacial lipoma comparable to previous reports. The lesion occurred predominantly in adult females and the buccal mucosa was the commonest orofacial site. Apart from the conventional lipoma, angiolipoma was the second most frequent histopathological variant of the lesion. Early surgical intervention and histopathological evaluation of clinically suspicious cases of orofacial lipoma is recommended to avoid facial disfigurement and to rule out a malignant lesion mimicking the benign type.